Biglycan in the Skeleton. (November 2020) - Kram, Vardit; Shainer, Reut; Jani, Priyam; Meester, Josephina A.N.; Loeys, Bart; Young, Marian F.
Small leucine rich proteoglycans (SLRPs), including Biglycan, have key roles in many organ and tissue systems. The goal of this article is to review the function of Biglycan and other related SLRPs in mineralizing tissues of the skeleton. The review is divided into sections that include Biglycan's role in structural biology, signaling, craniofacial and long bone homeostasis, remodeled skeletal tissues, and in human genetics. While many cell types in the skeleton are now known to be affected by Biglycan, there are still unanswered questions about its mechanism of action(s).